Wieś gnieźnieńska w powstaniu Wielkopolskim 1918/1919 - Karwat, Janusz (Studia Europaea Gnesnensia, 2022)
The paper outlines how the citizenry of the Gniezno countryside contributed in the Greater Poland Uprising, showing the key role that the region played in the victorious military action. The reader is acquainted with the leading insurgent figures and national activists of all municipalities of the then counties of Gniezno and Witkowo.